Effect of low-pressure pneumoperitoneum on pain and inflammation in laparoscopic cholecystectomy: a randomized controlled clinical trial - Mohammad Rashdan; Salam Daradkeh; Mutasim Al-Ghazawi; Jareer Heider Abuhmeidan; Azmi Mahafthah; Ghada Odeh; Mohammad Al-Qaisi; Ikram Salameh; Shahed Halaseh; Lana Al-Sabe; Yousef B. Ahmad; Tuqa Al-Ghazawi; et al. (BMC Research Notes, 2023)
Abstract Objective We aim to assess the effect of low-pressure pneumoperitoneum on post operative pain and ten of the known inflammatory markers. Background The standard of care pneumoperitoneum set pressure in laparoscopic cholecystectomy is set to 12–14 mmHg, but many societies advocate to operate at the lowest pressure allowing adequate exposure of the operative field. Many trials have described the benefits of operating at a low-pressure pneumoperitoneum in terms of lower post operative pain, and better hemodynamic stability. But only few describe the effects on inflammatory markers and cytokines. Methods A prospective, double-blinded, randomised, controlled clinical trial, including patients who underwent elective laparoscopic cholecystectomy. Patients randomised into low-pressure (8–10 mmHg) vs. standard-pressure (12–14 mmHg) with an allocation ratio of 1:1. Perioperative variables were collected and analysed. Results one hundred patients were allocated, 50 patients in each study arm. Low-pressure patients reported lower median pain score 6-hour post operatively (5 vs. 6, p-value = 0.021) in comparison with standard-pressure group. Eight out of 10 inflammatory markers demonstrated better results in low-pressure group in comparison with standard-pressure, but the effect was not statistically significant. Total operative time and surgery difficulty was not significantly different between the two groups even in the hands of inexperienced surgeons. Conclusion low-pressure laparoscopic cholecystectomy is associated with less post operative pain and lower rise of inflammatory markers. It is feasible with comparable complications to the standard of care. Registered on ClinicalTrials.gov (NCT05530564/ September 7th, 2022).